2013
DOI: 10.1017/s1366728913000746
|View full text |Cite
|
Sign up to set email alerts
|

Lexical-semantic skills in bilingual children who are becoming English-dominant: A longitudinal study

Abstract: Link to this article: http://journals.cambridge.org/abstract_S1366728913000746How to cite this article: LI SHENG (2014). Lexical-semantic skills in bilingual children who are becoming English-dominant: A longitudinal study .Twenty-seven Mandarin-English bilingual children participated in picture identification and picture naming tasks at two time points, 16 months apart. The younger children (mean age = 4 years) showed greater gains over time than the older children (mean age = 6 years 10 months) in English le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
6
16
0
Order By: Relevance
“…In other words, the collaborative language policy promotes an additive bilingual environment in Hong Kong, which may have enabled students to maintain their first language while adding a second one and such additive environment is also facilitating the transfer between the two langauges (Lambert, 1975). By contrast, studies of Mandarin-English bilingual children in the United States indicated an early stagnation of these children's Mandarin skills as these children were focusing on learning English and becoming English-dominant (Sheng, 2014). L1, or heritage language attribution has been found in other bilingual groups in the North America context.…”
Section: Moderator Effect Of Geographic Location and Grade Levelmentioning
confidence: 87%
See 2 more Smart Citations
“…In other words, the collaborative language policy promotes an additive bilingual environment in Hong Kong, which may have enabled students to maintain their first language while adding a second one and such additive environment is also facilitating the transfer between the two langauges (Lambert, 1975). By contrast, studies of Mandarin-English bilingual children in the United States indicated an early stagnation of these children's Mandarin skills as these children were focusing on learning English and becoming English-dominant (Sheng, 2014). L1, or heritage language attribution has been found in other bilingual groups in the North America context.…”
Section: Moderator Effect Of Geographic Location and Grade Levelmentioning
confidence: 87%
“…Chinese (or heritage language) instruction, when available, is provided on an informal basis through the family or the community. These after-school or weekend heritage language programs tend to be very short in duration and insufficient to support the continuous growth of their L1 (Sheng, 2014). At the other end, in Mainland China and Taiwan, Mandarin Chinese is the official language in the greater society and the language of instruction in school.…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Posthoc tests showed significantly higher ratings in English than Mandarin for the seven-year-old group (Mean difference=.56, p<.01, 95% CI=.19-.94) and no difference between Mandarin and English proficiency rating in the other two groups. The apparent inconsistency between parental subjective rating and performance on an objective naming task for the five-and six-year-old groups may reflect an earlier shift towards English dominance in picture naming than in general oral proficiency (Sheng, 2014). Notes.…”
Section: Participantsmentioning
confidence: 99%
“…Given previous findings of cross-language associations in bilingual children’s vocabulary development (Kan & Kohnert, 2008; Kohnert, 2010; Sheng, 2012; Sheng et al, 2012), we were also interested in possible cross-language facilitation in semantic convergence in the current group of bilingual children.…”
mentioning
confidence: 99%